Impact of Dividend Policy on Share Price of Commercial Bank in Nepal (The International Research Journal of Management Science, 2018)
The purpose of this study is to examine the impact of dividend policy on the share price of commercial bank in Nepal. The study is based on pooled cross sectional data of 10 commercial banks. Banks were selected on the basis of their performance on stock market of Nepal, i.e. top gainers and top losers and data are collected from Nepalese commercial banks listed in NEPSE from the F/Y 2012/13 to F/Y 2016/17. The paper investigates the relationship between dividend announcement, EPS, P/E ratio, DPR, on stock price by using Descriptive Statistics, Correlation and Regression, ANOVA and Wilcoxon Signed Rank Test. The articles conclude that except DPR, the other factors like EPS, P/E ratio have positive relationship with stock price among them P/E is the strongest factor that affects the share price in case of top gainer commercial banks whereas EPS, P/E ratio and DPR have positive influence on stock price among them DPR is the strongest factor that affects the share price in case of top loser bank.